Synopsis: Public investment for Rwanda's inclusive agricultural transformation: A midterm assessment of the contribution of PSTA4 - Aragie, Emerta A.; Diao, Xinshen; Spielman, David J.; Thurlow, James; Mugabo, Serge; Rosenbach, Gracie; Benimana, Gilberthe Uwera (International Food Policy Research Institute, 2022)
Rwanda’s fourth Strategic Plan for the Transformation of Agriculture (PSTA 4), which extends from 2018 to 2024, is currently at its midpoint. This note highlights the contribution of PSTA 4 in its first half (2018–2021) to four key development outcomes: economic growth, job creation, poverty reduction, and diet quality improvement.